A cultural atlas of vocal variation: yellow-naped amazons exhibit contact call dialects throughout their Mesoamerican range - Genes, Molly K.; Araya-Salas, Marcelo; Dahlin, Christine R.; Wright, Timothy F. (Frontiers in Bird Science, 2023)
Vocal dialects are a taxonomically widespread phenomenon which are typically only studied in a portion of a species' range. Thus, it is difficult to infer whether a geographic pattern of vocal dialects observed in one part of a species' range are typical across the range or whether local conditions influence their presence or absence. We examined the yellow-naped amazon, Amazona auropalliata, a parrot species with remarkable vocal learning capabilities. Although this species' native range spans across Mesoamerica, only Costa Rican populations have been evaluated long-term. Previous studies have shown that these populations have geographically and temporally stable vocal dialect patterns. Without data on populations outside of Costa Rica, it is impossible to know whether vocal dialects are present in northern range populations, and whether they show similar geographic structure to southern range populations. We recorded yellow-naped amazon contact calls at 47 different sites across the species' range between 2016 and 2019 and evaluated them for the presence of dialects. We visually classified 14 contact call types based on spectrographic similarity and used spectrographic cross-correlation, principal component analysis, and Mantel-based spatial autocorrelations to assess acoustic similarity; we also evaluated the robustness of our findings using simulated data. The results from our study show that the vocal patterns previously seen in Costa Rica are also present in northern range populations, supporting our hypothesis that this species has vocal dialects throughout its Mesoamerican range. Call types were regionally specific (e.g., vocal dialects occurred) across the range, and no call types were repeated across multiple regions. We did, however, observe distinctive structural characteristics that are found in multiple call types, suggesting that different call types stem from a common origin. Alternatively, similarity in the acoustic features of call types may also be a result of physiological and anatomical features that are common to all members of the species. Vocal dialects in this species are likely maintained through a tendency toward philopatry and matching call types to enhance social identification.